The body economic : life, death, and sensation in political economy and the Victorian novel - Gallagher, Catherine (Princeton, N.J. : Princeton University Press, 2006)
The Body Economic revises the intellectual history of nineteenth-century Britain by demonstrating that political economists and the writers who often presented themselves as their literary antagonists actually held most of their basic social assumptions in common. Catherine Gallagher demonstrates that political economists and their Romantic and early-Victorian critics jointly relocated the idea of value from the realm of transcendent spirituality to that of organic ""life, "" making human sensations--especially pleasure and pain--the sources and signs of that value. Classical political econom
The Romantics and the political economists -- Bioeconomics and somaeconomics : life and sensation in classical political economy -- Hard times and the somaeconomics of the early Victorians -- The bioeconomics of Our mutual friend -- Daniel Deronda and the too much of literature -- Malthusian anthropology and the aesthetics of sacrifice in Scenes of clerical life.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Dickens, Charles, -- 1812-1870 -- Knowledge -- Economics; Eliot, George, -- 1819-1880 -- Knowledge -- Economics; Eliot, George, -- 1819-1880 -- Knowledge -- Economics; Dickens, Charles, -- 1812-1870 -- Knowledge -- Economics; Dickens, Charles, -- 1812-1870 -- Et l'économie politique; Eliot, George, -- 1819-1880 -- Et l'économie politique; Dickens, Charles, -- 1812-1870; Eliot, George, -- 1819-1880; English fiction -- 19th century -- History and criticism; Economics in literature; Economics -- Great Britain -- History -- 19th century; Great Britain -- Economic conditions -- 19th century; Senses and sensation in literature; Human body in literature; Death in literature; Roman anglais -- 19e siècle -- Histoire et critique; Économie politique dans la littérature.; Économie politique -- Grande-Bretagne -- Histoire -- 19e siècle.; Sens et sensations dans la littérature.; Corps humain dans la littérature.; Mort dans la littérature.; Grande-Bretagne -- Conditions économiques -- 19e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Death in literature; Economic history; Economics; Economics in literature; English fiction; Human body in literature; Senses and sensation in literature; Great Britain; 1800-1899; Criticism, interpretation, etc; History